Nutritional and functional characterization of different oat (Avena sativa L.) cultivars. Issue 1 (1st January 2020) - Ibrahim, Muhammad Suhail; Ahmad, Asif; Sohail, Asma; Asad, Muhammad Javaid
ABSTRACT: Oats are increasingly recognized as super food owing to the presence of multiple healt h promoting substances. Five indigenous oat cultivars S2000, PD2LV65, SGD2011, Avon and SGD81 were characterized physico-chemically and nutritonally. Avon showed the maximum (12.69 g100 g- 1 dry solids) protein content indicating potential to be used as protein source for animal and human food, whereas SGD-81 excelled incrude fiber contents (17.83 g100 g- 1 dry solids). Avon showed the highest fat contents (6.67 g100 g- 1 dry solids). Maximum moisture contents showed by the SGD-81 (9.29 g100 g- 1 dry solids). SGD-2011 showed maximum ash contents (6.02 g100 g- 1 dry solids). S-2000 showed the maximum nitrogen-free extract (60.78 g100 g-1 dry solids) and thousand grain weight (36.74 g). Highest Zn (0.176 mg g- 1 of dry solids) and Fe (0.032 mg/g- 1 dry solids) contents were found in Avon. Avon showed maxium bulk density of 0.76 g/cc and Avon grains had maximum length and breadth ratio (2.93). The highest water absorption capacity, oil absorption capacity and emulsion stability were shown by SGD-81 as 188.33%, 218.754% and 73.13%, respectively. The highest foaming capacity was shown by S-2000 (20%) and the highest emulsion activity was shown by SGD 2011 (56.84%). Amino acid profiling showed the highest outcome 105.67 g kg −1 of dry solids by SGD-2011.While least 99.13 g kg −1 of dry solids depicted by S2000. Total phenolic contents varied from 36.07 to 59.6 mg of gallic acid equivalent (GAE), total flavonoids (754.16–1056.66 mg of quercetin equivalent:QE), TfoC (663.75–697.5 mg QE), % scavenging activity (24.33–55.88%) and anthocyanin contents of 0.5–2.87 mg of C3 G kg −1 . SGD-81 was loaded with promising nutraceutical potential. SGD-81 would be good substitute of fiber and also loaded with other promising functional attributes including total flavonoid contents, total phenolic contents, total flavonol conetnts and anthocyanin contents. There is great potential for value addition of the oat cultivar SGD-81. Abbreviation: NFE: Nitrogen-Free Extract; WAC: Water absorption capacity; NFE: Nitrogen-Free Extract; OAC: Oil absorption capacity; TGW: Thousand grain weight; FC: foaming capacity; BD: Bulk density; EA: Emulsion activity; L/B ratio: Length and breadth ratio; TFC: Total flavonoid contents; TFoC: Total flavonol contents; DPPH-2, 2-Diphenyl-1-Picrylhydrazyl; NAA: Nonessential amino acid; TAA: total amino acids; ES: Emulsion stability; TPC: Total phenolic contents; ppm: parts per million; EAA: Essential amino acids; mg of C3G kg −1 -milligram of Cyanidine 3-glucoside per kilogram